{{page>:defs}} ====== Gauss-Markov Theorem and other results ====== ===== Basics on linear algebra ===== Let $\b{X}$ be a $n \times p$ matrix with real-valued entries. We define $\img(\b{X})=\set{\b{X}\b{y}}{\b{y} \in \rset^p}$ and $\ker(\b{X})=\set{\b{y} \in \rset^p}{\b{X}\b{y}=0}$. We can note that $\img(\b{X})$ and $\ker(\b{X}^T)$ are subspaces of $\rset^n$. $\itemm$ $\img(\b{X}) \stackrel{\perp}{\oplus} \underbrace{\img(\b{X})^\perp}_{\ker(\b{X}^T)}= \rset^n$. Otherwise stated, $x$ is the orthogonal projection of $y$ on $\b{X}$ if and only if we have the two properties $x \in \img(\bf{X})$ and $(y-x) \in \ker(\b{X}^T)$. The fact that $\ker(\b{X}^T)$ is the orthogonal complement of $\img(\b{X})$ stems from the following remark: $z \in \img(\b{X})^\perp$ is equivalent to the fact that $\b{X}_i^T z=0$ where $\b{X}_1,\ldots,\b{X}_p$ are the column vectors of $\b{X}$ and this in turn is equivalent to $\bf{X}^Tz=0$. $\itemm$ Denote by $P_{\img(\b{X})}$ the matrix of the orthogonal projection on $\img(\b{X})$. By abuse of notation, we also write $P_{\b{X}}$. We have $P_\b{X}=P_\b{X}^2=P_\b{X}^T$ and we can also note that $P_\b{X}=I$ on $\img(\b{X})$. $\itemm$ An orthogonal projection is uniquely determined by the subspace on which it projects. This implies in particular the following property. Assume that $\b{X}$ is a $n \times p$ matrix and $\b{W}$ is a $n \times k$ matrix where we can possibly have $k \neq p$. As soon as $\img(\b{X})=\img(\b{W})$, we have $P_\b{X}=P_{\img(\b{X})}=P_{\img(\b{W})}=P_\b{W}$ {{anchor:star}} $\itemm$ By the Pythagore identity, for all $a\in \rset^n$, we have $\|a\|^2=\|P_\b{X}a\|^2+\|(I-P_\b{X})a\|^2$ ($\star$) showing that $\|a\|\geq \|P_\b{X}a\|$ with equality only if $P_\b{X}a=a$. $\itemm$ $\b{X}^g$ is a pseudo inverse of $\b{X}$ (and we note $\b{X}^g$) iff $\b{X} \b{X}^g \b{X}=\b{X}$ or, equivalently, for all $\lambda \in \img(\b{X})$, $\b{X} \b{X}^g \lambda=\lambda$. We admit that a pseudo inverse always exists. /* $\itemm$ $\ker(\b{X}^T \b{X})= \ker(\b{X})$[(This follows from $\lambda^T \b{X}^T \b{X}\lambda=\|\b{X} \lambda\|^2$ for all $\lambda \in \rset^p$)] and translating this equality on the orthogonal complement of these spaces, we get also $\img(\b{X}^T\b{X})=\img(\b{X}^T)$. */ ===== Ordinary Least squares (OLS) estimator ===== Let $\b{y}$ be a vector of size $n$ and $\b{X}$ a $n \times p$ matrix. Since $P_\b{X}\b{y}$ is in $\img(\b{X})$, it can be written as $P_\b{X} \b{y}=\b{X} \b{\hat b}$ for some $\b{\hat b} \in \rset^p$. __The fundamental result__. **Theorem**. The following properties are equivalent * $\b{\hat b}$ is such that $P_\bf{X} \b{y}=\b{X}\b{\hat b}$ * $\b{\hat b}$ is such that $\|\b{y}-\b{X}\b{\hat b} \|=\inf_{b \in \rset^p}\|\b{y}-\b{X}\b{b}\|$ * $\b{\hat b}$ satisfies the **normal equations**[(For the third point, the equivalence with the other statements follows from the fact that for all $\b{b}$, $(\b{y}-\b{X}\b{\hat b})\perp \b{X}\b{b}$ iff for all $\b{b}$, $\b{b}^T\b{X}^T(\b{y}-\b{X}\b{\hat b})=0$ which is equivalent to $\b{X}^T(\b{y}-\b{X}\b{\hat b})=0$, which are the normal equations.)]: $\bf{X}^T\bf{X} \b{\hat b}=\bf{X}^T \b{y}$. Moreover, $P_\b{X}=\bf{X}(\bf{X}^T \bf{X})^g\bf{X}^T$ for any choice of the pseudo inverse $(\bf{X}^T \bf{X})^g$. A side effect of this theorem is that $\bf{X}(\bf{X}^T \bf{X})^g\bf{X}^T$ does not depend on the choice of the pseudo inverse $(\bf{X}^T \bf{X})^g$. The only difficult part is to show that the matrix defined in the last statement is the one of the orthogonal projector onto $\img(\b{X})$. Set $M=\bf{X}(\bf{X}^T \bf{X})^g\bf{X}^T$ and let $\b{y} \in \rset^n$. We show that $M\b{y}=P_\bf{X}\b{y}$ by checking successively that $M\b{y} \in \img(\b{X})$ and $\b{y} -M\b{y} \in \ker(\b{X}^T)$. The first statement is straightforward: $M \b{y}=\b{X}\lr{(\bf{X}^T \bf{X})^g\bf{X}^T \b{y}} \in \img(\b{X})$. The second statement is in two steps: * $\b{X}^T(I-M)\b{X}=\b{X}^T\b{X}-\b{X}^T\b{X}(\bf{X}^T \bf{X})^g\b{X}^T\b{X}=0$ showing that $\b{X}^T(I-M)=0$ on $\img(\b{X})$. * Moreover, for $z \in \ker(\b{X}^T)$, $\b{X}^T(I-M)z=\underbrace{\bf{X}^T z}_{0}-\b{X}^T\bf{X}(\bf{X}^T \bf{X})^g\underbrace{\bf{X}^T z}_{0}=0$. Finally, $\b{X}^T(I-M)=0$ on $\img(\b{X})$ and $\ker(\b{X}^T)$ and therefore on $\img(\b{X}) \oplus \ker(\b{X}^T)=\rset^n$ so that $(I-M)\b{y} \in \ker(\b{X}^T)$. This concludes the proof. We can now give the general solutions of the normal equations. __Solving the Normal equations__. **Theorem**. The following equivalence holds true. $\b{\hat b}$ solves the normal equations iff there exists $\b{z}\in \rset^p$ such that $$ \b{\hat b}=(\bf{X}^T \bf{X})^g\bf{X}^T \b{y}+ \lrb{I-(\bf{X}^T \bf{X})^g\bf{X}^T \b{X}} \b{z} $$ for some pseudo-inverse $(\bf{X}^T \bf{X})^g$. Indeed, if $\b{\hat b}$ can be written as in the statement of the Theorem, then applying $\b{X}$ we get $$ \b{X}\b{\hat b}=P_\b{X} \b{y}+ \lr{\underbrace{\b{X}-P_\b{X} \b{X}}_{0}}\b{z}=P_{\b{X}} \b{y}, $$ showing that $\b{\hat b}$ solves the normal equations by the fundemental result. Conversely, assume that $\b{\hat b}$ solves the normal equations. Then choosing any pseudo inverse $(\bf{X}^T \bf{X})^g$, \begin{align*} \b{\hat b}&=(\bf{X}^T \bf{X})^g\bf{X}^T \b{y}+ \b{\hat b}- (\bf{X}^T \bf{X})^g\underbrace{\bf{X}^T \b{y}}_{\b{X}^T\b{X} \b{\hat b}} &=(\bf{X}^T \bf{X})^g\bf{X}^T \b{y}+ \lrb{I-(\bf{X}^T \bf{X})^g\bf{X}^T \b{X}} \b{\hat b} \end{align*} which completes the proof. ===== Estimability and the Gauss-Markov theorem ===== We now consider $\b{y}=\b{X}\b{b}+e$ where $e$ is a zero mean vector with covariance matrix $\sigma^2 I_n$. We say that $\lambda^T \b{b}$ is //**estimable**// if there exists $a\in \rset^n$ such that $a^T\b{y}$ is an unbiased estimator of $\lambda^T \b{b}$, which is equivalent to $\lambda^T \b{b}=a^T\b{X}\b{b}$ for all $\b{b}\in \rset^p$ and therefore to $\lambda^T=a^T\b{X}$. __The Gauss-Markov Theorem__ . For any linear unbiased estimator $a^T \b{y}$ of $\lambda^T \b{b}$, $$ \Var(a^T \b{y})\geq \Var(\lambda^T \b{\hat b}) $$ where $\hat b$ is the least square estimator of $\b{b}$. We then say that $\lambda^T \b{\hat b}$ is BLUE (Best Linear Unbiased Estimator). Moreover, the equality only holds if $a^T \b{y}=\lambda^T\b{\hat b}$, saying that the BLUE is unique. Note that since $a^T\b{y}$ is an unbiased estimator of $\lambda^T \b{b}$, we have $\lambda^T =a^T\b{X}$. This implies that $$ \lambda^T \b{\hat b}=a^T\b{X}\b{\hat b}=a^T P_\b{X}\b{y} \quad (\star) $$ Then, $\PE[\lambda^T \b{\hat b}]=a^T P_\b{X} \b{X}\b{b}=a^T \b{X}\b{b}=\lambda^T \b{b}$, showing that $\lambda^T \b{\hat b}$ is unbiased. Moreover, using again ($\star$), $\lambda^T \b{\hat b}=a^T P^T_\b{X}\b{y}=(P_\b{X}a)^T \b{y}$ so that, (see [[world:gauss_markov#$\star$]]) $$ \Var(\lambda^T \b{\hat b})= \sigma^2 \|P_\b{X}a\|^2 \leq \sigma^2 \|a\|^2 =\Var(a^T \b{y}) $$ with equality only if $P_\b{X}a=a$ which implies $\lambda^T \b{\hat b}=(P_\b{X}a)^T \b{y}=a^T \b{y}$. In the curse of the proof, we have seen that if $\lambda^T \b{b}$ is estimable, then choosing $a$ such that $\lambda^T=a^T\b{X}$, $$ \Var(\lambda^T \b{\hat b})= \sigma^2 \|P_\b{X}a\|^2=\sigma^2 a^T P_\b{X}^T P_\b{X} a=\sigma^2 a^T P_\b{X} a=\sigma^2 a^T \b{X} (\b{X}^T\b{X})^g \b{X}^T a=\sigma^2 \lambda^T (\b{X}^T\b{X})^g \lambda, $$ and a side effect is that $\lambda^T (\b{X}^T\b{X})^g \lambda$ does not depend on the chosen pseudo-inverse whenever $\lambda \in \img(\b{X}^T)$. ---- [[https://youtu.be/n8ROeIlZkSI|Video of a short course on the Gauss Markov Theorem]]